If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4b = -1b + -9 Reorder the terms: -4b = -9 + -1b Solving -4b = -9 + -1b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add 'b' to each side of the equation. -4b + b = -9 + -1b + b Combine like terms: -4b + b = -3b -3b = -9 + -1b + b Combine like terms: -1b + b = 0 -3b = -9 + 0 -3b = -9 Divide each side by '-3'. b = 3 Simplifying b = 3
| 7z-1/2=3z | | 150+2x=45-1x | | -3t=7-4t | | 9N+10Y=200 | | 150+2x=195-1k | | 3v+8=4v | | x^3y=-4 | | 6x+3x^2=500 | | (3y-5)(5y+6u-4)= | | 6n-11=9+n | | 100x-75=50x+75 | | 9(x-a)=y | | 3x+6x^2=500 | | 4x+6x^2=500 | | r=(b+a)m | | 121=i | | ((x-2)^(2)(x^(2)-1))/((x-1)^(2)(x^(2)-4)) | | -(5/8)a-20=-10 | | 3(x+8)=y | | 150x-(3100+5x+.1x^2)=0 | | x=1*0.75 | | (2x+1)(1+x)=2(1-x)+6 | | 7+-5=6+-2 | | 6(x+4)+4=-14 | | 3h=21/2 | | 4x^2+32x=-65 | | 8.4=-logx | | 495.4/713.36 | | 6.4=2p | | m-22/4-4m-27/5=1 | | x^2+16-16x+x^2=4-4x+x^2 | | 3b/2b |